UTHM Students’ Event Management System - Ulul Azmi, Putera Al-Amin Shah; Ibrahim, Noraini (Applied Information Technology And Computer Science, 2021)
Universiti Tun Hussein Onn Malaysia (UTHM) has over 50 student clubs and society as registered by UTHM Student Affairs and Alumni Office (HEPA).Pusat Sukan UTHM (PSU) is the party that is responsible in approving or rejecting the clubs’ co-curricular event applications. Currently, applications are processed by means of a paper filing method. The present process requires considerable time and effort. Thus, UTHM Student’ Event Management System (USEM) is developed to manage all the data related to the various co-curricular events that take place in UTHM. The system can be used to support a centralised database of all events. This system is developed through activities within the evolutionary software prototyping model where three iterations were involved. USEM is a web-based system that has been developed using PHP programming language and MySQL as database software. USEM allows for reduced data entry work, easy retrieval of information, reduced errors due to human intervention, user friendly interface to enter the data, fast finding of information request and easy to access anywhere. The test result shows that, this system helps PSU and student clubs to manage co-curricular events efficiently.